Pengembangan Suplemen Bahan Ajar IPAS Materi Harmoni dan Ekosistem Siswa Kelas V - Kriswanto, Dafi; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In general, this research aims to produce a product in the form of a supplement teaching materials for the Science and Social subject on Harmony and Ecosystems students grade Vth as accompanying teaching materials in the learning process at State Elementary School 17 Pontianak City. The method used in this research is R&D (Research and Development) with a mixed method and using the ADDIE model with five stages analysis, design, development, implementation, and evaluation. All data obtained in this research came from the homeroom teacher, 27 students and two experts. The techniques in this research to get all the data used interviews, test and questionnaires. Validation results by the first validator for products obtained an average of 4.93 with a percentage of 98.6% (Very Valid) and the second Validator obtained an average of 4.86 with a percentage of 97.2% (Very Valid). The results from the small group product trials obtained an average of 4.74 with a percentage of 95% (Very Good) and the large group product trials obtained an average of 4.65 with a percentage of 93% (Very Good). The results of the response questionnaire to homeroom teacher obtained an average of 4.53 with a percentage of 90.6% (Very Good).